Location strategies. Colombian art after modern art - Valencia, Luis Fernando (Estudios de Filosofía, 1996)
The article arms to expose the circumstances identifying colombian art after modern art. The author recalls the philosophical reflection about the end of art, which is important to understand modernity and modern art, whose concepts on art, artist, context and form are derived from Hegel’s Lessons of Aesthetics. Hence, colombian art after modernity and its features are studied in its condition of historical reality.